Edukasi Strategi Pemasaran UMKM Di Desa Ulu Lakara Kec. Palangga Selatan - Isalman; Ambo Upe; Juharsah; Nurul Ittaqullah (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Micro, small and medium enterprises (MSMEs) have an important and strategic role to move the community's economy in conditions of economic crisis or pandemic. The sizeable absorption of MSMEs contributes to an increase in people's income which in turn reduces unemployment and poverty. MSMEs in Ulu Lakara village are still on the scale of Livelyhood Activity, and Micro Enterprise. One of the weaknesses of MSMEs at this scale is their low knowledge of product marketing. Marketing strategy has an important role for MSMEs to achieve a sustainable competitive advantage. The solution that can be given is to provide training on product marketing strategies both offline and online marketing. This activity is expected to provide knowledge about the urgency of giving an attractive business name or product brand, knowledge of the basics in segmenting, targeting and positioning, knowledge of the marketing mix, to skills in marketing products online